Six innings : a game in the life - Preller, James (Feiwel and Friends, 2008)
Earl Grubb's Pool Supplies plays Northeast Gas & Electric in the Little League championship game, while Sam, who has cancer and is in a wheelchair, has to call the play-by-play instead of participating in the game.